2018
DOI: 10.21614/sgo-23-2-121
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Serum Cystatin C, Urinary Kidney Injury Molecule-1 and MELD plus Score Predicts Early Acute Kidney Injury after Liver Transplantation

Abstract: Introduction: Acute kidney injury (AKI) following liver transplantation (LT) is a frequent complication and is associated with increased morbidity and mortality. Aim: To investigate whether the levels of urinary KIM-1 and serum Cystatin C are able to predict early occurrence (within the first 48 hours) of the post-LT renal dysfunction. Methods: The study was conducted on 25 recipients transplanted in the Fundeni Clinical Institute between May 2016 and February 2017. Serum Cystatin C, urinary KIM-1 and serum cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The study confirmed the high predictive value of pNGAL (AUC 0.84 at 4 h and 0.86 at 8 h after ICU admission), and the somewhat weaker value of uNGAL (0.79 right after the procedure, 0.80 at 4 h, and 0.76 at 8 h after ICU admission), while uKIM-1 and uGST failed to detect AKI. Similar results were obtained in a recent study by Tudoroiu et al [43].…”
Section: Kim-1supporting
confidence: 93%
“…The study confirmed the high predictive value of pNGAL (AUC 0.84 at 4 h and 0.86 at 8 h after ICU admission), and the somewhat weaker value of uNGAL (0.79 right after the procedure, 0.80 at 4 h, and 0.76 at 8 h after ICU admission), while uKIM-1 and uGST failed to detect AKI. Similar results were obtained in a recent study by Tudoroiu et al [43].…”
Section: Kim-1supporting
confidence: 93%
“…Cystatin C is a non-glicolized protein with small molecular weight (13.3 kDa), a hundred times bigger than creatinine. It is produced at a constant rate by all the nucleated cells, and is freely filtered by glomeruli and minimally linked to proteins, and is not reabsorbed in the systemic circulation after the filtering (30) . Furthermore, it has shown promise as a replacement for serum creatinine in estimation of glomerular filtration rate (GFR).…”
Section: Discussionmentioning
confidence: 99%
“…In O'Riordan et al study, 30-day mortality in patients with AKI who required renal dialysis was 4 times higher compared with mortality in those without renal dysfunction (5). Multiple factors can predispose to AKI after LT, such as: pre-transplant renal dysfunction, high blood pressure and pre-and post-transplant diabetes, hepatitis C infection, graft quality, severity of liver disease, nephrotoxic drugs, especially the immunosuppression, pre-LT hypoalbuminemia, duration of the intraoperative vascular clamping, cold ischemia time, intraoperative transfusion requirement, perioperative hypotension and vasopressor support need, duration of surgery (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Unlike other diseases, where new markers were discovered and used for diagnosis and staging, sCr remained the most common test in evaluating renal function.…”
Section: Introduction Introductionmentioning
confidence: 99%